Pengaruh Praktik Kerja Industri dan Minat Kerja Terhadap Kesiapan Kerja Pada Dunia Usaha dan Dunia Industri Siswa SMK - Siti Wahyuni; Fadjriah Hapsari; Mirna Herawati (Universitas Majalengka, 2021)
Teachers as educators are expected to continuously improve their professional abilities, especially in terms of preparing students or students to enter the world of work. However, there are still teachers who use conventional learning in delivering learning materials to students. As a result, students are less able to develop their cognitive, affective, and psychomotor abilities. One of the problems that occur is the lack of implementation of the implementation and delivery of materials that are adapted to the demands of the world of work. This study aims to analyze and test the truth of the hypothesis regarding the effect of industrial work practices (Prakerin) and work interest on the work readiness of class XII students of the Fashion Design Expertise Program at SMK Negeri 2 Depok. The research was conducted using quantitative methods. The population is class XII of the Fashion Design Expertise Program at SMK Negeri 2 Depok with a sample size of 60 students, with the sampling technique used is saturated sampling. The research instruments used were questionnaires and observation sheets. Data analysis techniques include multicollinearity test, heteroscedasticity, normality test, multiple linear regression, f test, t test, coefficient of determination and correlation coefficient. The results of the analysis and discussion show that Industrial Work Practices (X1) and Work Interest (X2) on Work Readiness (Y) have a strong influence, the correlation coefficient value is 0.750. Multiple linear regression analysis obtained the equation Y = 4.779 + 0.512 X1 + 0.306 X2. F test obtained Fcount = 36.532, so Ha1 is accepted. Partially (t-test) industrial work practices (X1) obtained tcount = 4.447 with a significance of 0.00 <0.05, so Ha2 is accepted. Interest in work (X2) obtained tcount = 3.318 with a significance of 0.00 <0.05, so Ha3 is accepted. Simultaneously (R2) industrial work practices and work interest have an effect on student work readiness, which is 54.6%